Corporate Restructuring: Empirical Evidence from Singapore - LIU, ZHI WAI (2015)
Corporate restructuring is one of the most challenging but widely researched areas in finance literature. A firm faces three restructuring choices: diversify, refocus or do nothing. Prior theoretical and empirical studies independently separate and examine the various determinants (i.e. firm-specific, industry-specific and general economic conditions) of restructuring decisions. This approach overlooks the important issue that determinants may simultaneously influence the restructuring decisions. Furthermore, prior studies provide inconclusive evidence with regards to investors’ reactions to restructuring announcements. Despite extensive research on corporate restructuring, little attention has been paid to empirically study corporate restructuring in Singapore. To rectify this deficiency, this study investigates the possible determinants that may be associated with the restructuring decisions and announcement effects of restructuring amongst Singapore-listed firms. The sample firms are listed on the Singapore Exchange and the time horizon extends from 2000 to 2011.